Synthesis and optimisation of a lignocellulosic biomass pre-processing system for thermochemical biorefineries - Goh, Wui Seng (2018)
Fossil resources are widely utilised as sources for energy and chemical productions by society. Despite of its vast usage, it is often also identified as non-sustainable resources due to its limited availability and its contribution to greenhouse gas emission. In such regards, biomass, particularly lignocellulosic biomass is identified as a promising renewable source of carbon that has potential to replace fossil resources in energy and chemical productions. Biorefinery or integrated biorefinery is a processing facility that uses biomass as feedstock to produce value-added products, such as energy, fuels and chemicals. Integrated biorefinery can also be regarded as a processing facility that jointly apply various types of biomass processing technologies that produces useful products from biomass. In such regards, one of the important research and development areas for biorefinery or integrated biorefinery is to synthesise and integrate wide spectrums of biomass processing technologies as a whole.